Qualitative and quantitative characterization of protein biotherapeutics with liquid chromatography mass spectrometry. Issue 6 (20th April 2016) - Qu, Miao; An, Bo; Shen, Shichen; Zhang, Ming; Shen, Xiaomeng; Duan, Xiaotao; Balthasar, Joseph P.; Qu, Jun
Abstract : In the last decade, the advancement of liquid chromatography mass spectrometry (LC/MS) techniques has enabled their broad application in protein characterization, both quantitatively and qualitatively. Owing to certain important merits of LC/MS techniques (e.g., high selectivity, flexibility, and rapid method development), LC/MS assays are often deemed as preferable alternatives to conventional methods (e.g., ligand‐binding assays) for the analysis of protein biotherapeutics. At the discovery and development stages, LC/MS is generally employed for two purposes absolute quantification of protein biotherapeutics in biological samples and qualitative characterization of proteins. For absolute quantification of a target protein in bio‐matrices, recent work has led to improvements in the efficiency of LC/MS method development, sample treatment, enrichment and digestion, and high‐performance low‐flow‐LC separation. These advances have enhanced analytical sensitivity, specificity, and robustness. As to qualitative analysis, a range of techniques have been developed to characterize intramolecular disulfide bonds, glycosylation, charge variants, primary sequence heterogeneity, and the drug‐to‐antibody ratio of antibody drug conjugate (ADC), which has enabled a refined ability to assess product quality. In this review, we will focus on the discussion of technical challenges and strategies of LC/MS‐based quantification and characterization of biotherapeutics, with the emphasis on the analysis of antibody‐based biotherapeutics such as monoclonal antibodies (mAbs) and ADCs. © 2016 Wiley Periodicals, Inc. Mass Spec Rev 36:734–754, 2017